P420 Long term efficacy of ustekinumab in Crohn's disease patients after vedolizumab failure. (21st January 2022) - Melotti, L; Dussias, N K; Belluzzi, A; Salice, M; Calabrese, C; Rizzello, F; Gionchetti, P
Abstract: Background: Ustekinumab (UST) and vedolizumab (VDZ) are approved biologic therapies for moderate-to-severe Crohn's disease (CD). Data regarding their comparative efficacy in patients previously treated with anti-TNF agents are available. However, data is lacking regarding their long-term effectiveness after failure of a second or third-line biologic treatment. Our aim is to evaluate ustekinumab efficacy after swapping from vedolizumab therapy for primary or secondary failure. Methods: We conducted a single-centre, retrospective study in CD patients treated with UST as third line biologic therapy who swapped from VDZ therapy upon failure between January, 2019 and October, 2021. We assessed clinical (HBI), laboratoristic (CRP), endoscopic (SES-CD) activity and use of steroids at the beginning of ustekinumab therapy and after, 12 months of treatment. We also collected data regarding previous biologic treatments. Clinical remission was defined as HBI <, 5, while clinical response was defined as a reduction of at least three points of HBI from baseline and/or the suspension of steroids. Results: Of, 43 patients treated with UST after VDZ failure, 26 had a minimum follow up of, 12 months and were included in the study. All patients had previously been treated with antiTNF agents. After, 12 months, 4 patients have suspended treatment for failure; among patients still on treatment, clinical remission was evident in, 63% (n = 14) of cases, 13 of them were also in laboratoristic remission. Endoscopy at, 12 months was available in, 11/14 patients in clinical remission; of these, 6 (55%) were in endoscopic remission. In patients who did not achieve clinical remission, 18% (n = 4) obtained clinical response. The last, 18% (n = 4) of patients persisted on therapy. Conclusion: Ustekinumab seems to be a viable and effective therapeutic option in patients with failure to multiple prior biologic therapies, obtaining deep remission after, 12 months of treatment in a large proportion of patients.